School principal leadership style in improving teacher performance of the junior high school in Banda Aceh - Musriadi, - (LPPM UNY, 2015)
The leadership style of the school principal is one of determinants factor inimproving teacher performance and education success in the school. This research study is aimed at describing the leadership of principals toward improving teachers' performances reï¬‚ ected on their responsibilities, discipline, and commitment as the performance indicators. The study uses a qualitative descriptive method. Data are collected by observation, interview and documentation. The subjects of the study are school principal and teachers. Findings show the following. 1) In improving teacher responsibilities, the principal of Junior High School in Banda Aceh maintains togetherness and socializes vision and mission of the school through discretionary leadership style and consultative leadership style. 2) In improving teacher disciplines, the principal of Junior High School Banda Aceh uses the discretionary leadershipstyle such as acting in ways that have been agreed upon and achieving goals setmore by subordinates. 3) In improving teacher commitment, the principal of Junior High School in Banda Aceh is being fair in distributing the duties or welfare which is directed to the regulation and program through discretionary leadership style which has the ability to inï¬‚ uence another to work together in achieving goals set by various activities which is much more given to the subordinate